Feminisme Peran Tokoh Perempuan dalam Sinetron Jangan Bercerai Bunda Disutradarai oleh Amin Ishaq dan Implikasinya pada Pembelajaran Cerpen di SMA - Septi Apriliani; Lazarus Linarto; Paul Diman; Alifiah Nurachmana; Patrisia Cuesdeyeni (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
The purpose of this study was to obtain an overview of the role of women in the soap opera Don't Divorce Mother directed by Amin Ishaq. The specific objectives of this study are: (1) describe the role of women as wives who accompany their husbands in the soap opera Don't Divorce Mother, (2) describe the role of women as mothers educators and coaches for their children in the soap opera Don't Divorce Mother, (3) describe the role of women as members of society in the soap opera Don't Divorce Mother, and (4) the implications for learning short stories in high school. The approach used in this study is a qualitative descriptive approach to reveal and analyze the picture of women's roles with the form of women's roles as wives who accompany their husbands, women's roles as mothers, educators and coaches for their children, and women's roles as community members. This study uses the theory of Katjasungkana (1989) in this theory there are five roles of women, namely; (1) Women as wives who accompany husbands, (2) Women as mothers educators and coaches for their children; (3). Women as housekeeping mothers; (4) Women as labor/breadwinners; (5) Women as members of society, but after conducting research, researchers obtained three forms of data contained in the soap opera Don't Divorce Mother, namely (1) the form of women's roles as wives who accompany their husbands. (2) the manifestation of women's role as mothers, educators and coaches for their children. (3) the role of women as members of society. As well as (4) the implications for short story learning in high school, especially in K.D 3.9 which is related to the material of analyzing the building blocks of short stories in short story collection books. This is in accordance with soap operas with the theme of women's feminism, the most dominant data obtained is w.